Jasser Auda's Multidimensional System (Ta'addud Al-Ab'ad) in Reconciling Contradictory Arguments - Wakhidah, Nur (Journal of Educational Sciences, 2025)
The study explores Jasser Auda’s concept of the multidimensional system (ta‘addud al-ab‘ad), which represents a major methodological innovation in contemporary Islamic legal thought, particularly in reconciling apparently contradictory arguments. Auda’s systemic framework views Islamic law as a dynamic and open structure composed of interrelated dimensions textual, contextual, rational, moral, and purposeful (maqāṣidiyyah). This research aims to analyze how Auda’s multidimensional approach functions epistemologically to harmonize conflicting evidences while positioning maqāṣid al-sharī‘ah as the normative axis of interpretation. Using a qualitative research design with a critical hermeneutics and systems-thinking paradigm, the study examines Auda’s major works Maqasid al-Shariah as Philosophy of Islamic Law: A Systems Approach, Fiqh al-Maqasid, and Reclaiming the Maqasid al-Shariah through in-depth content analysis of primary and secondary sources. The findings reveal that Auda’s multidimensional system not only reconciles divergent legal arguments but also promotes a more adaptive, integrative, and value-oriented ijtihad process. It repositions Islamic law as a living system responsive to social dynamics while maintaining its normative authenticity. This approach contributes to the renewal of Islamic epistemology toward a holistic, contextual, and maqāṣid-based paradigm.